1989
DOI: 10.1007/bf00451643
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the pharmacokinetics of chlorambucl and prednimustine in patients using a new high-performance liquid chromatographic assay

Abstract: Following the oral administration of either chlorambucil/prednisolone or prednimustine to patients, the plasma levels of free chlorambucil and phenylacetic acid mustard, the beta-oxidation product of chlorambucil, were measured using a new high-performance liquid chromatographic (HPLC) assay. This assay permitted the simultaneous detection of the analyzed compounds with a lower limit of detection of 30 ng/ml. The pharmacokinetics of chlorambucil and phenylacetic acid mustard were found to be entirely different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
16
2

Year Published

1991
1991
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 14 publications
3
16
2
Order By: Relevance
“…Probably due to a longer half-life of terminal elimination, approximated plasma clearance of chlorambucil in our study was less than those reported in the literature: 1.8 versus 2.6 ml/min./kg (Oppitz et al 1989;Benet et al 1996). The observation that AUC¬ was reduced only in those patients with a relatively high AUC at start suggests saturable induction of those enzymes involved in chlorambucil metabolism.…”
Section: Discussioncontrasting
confidence: 75%
See 3 more Smart Citations
“…Probably due to a longer half-life of terminal elimination, approximated plasma clearance of chlorambucil in our study was less than those reported in the literature: 1.8 versus 2.6 ml/min./kg (Oppitz et al 1989;Benet et al 1996). The observation that AUC¬ was reduced only in those patients with a relatively high AUC at start suggests saturable induction of those enzymes involved in chlorambucil metabolism.…”
Section: Discussioncontrasting
confidence: 75%
“…Chlorambucil and phenylacetic acid mustard plasma concentrations were measured using an isocratic reversed-phase HPLC method modified from previous protocols (Zakaria & Brown 1982;Adair et al 1985;Oppitz et al 1989). The HPLC equipment consisted of a Varian 5000 pump, a UV-detector (Varian UV-100, 254 nm) and a Shimadzu C-R5A integrator.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…While the bio availability of chlorambucil and prednisolone is more than 70% [7. 25, 32], previous studies found that the availability of these compounds from prednimustine ranged from 20 to 50% [5,28,32,33,35].…”
Section: Discussionmentioning
confidence: 99%